Factors Influencing Liquidity Risk of Islamic Banks in Indonesia : A Systematic Literature Review - Pranoto Effendi (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
Liquidity issues have become crucial in the banking sector during the global economic recovery following the COVID-19 pandemic, presenting significant challenges that Islamic banks must proactively address. This article systematically examines the factors influencing liquidity risk in Islamic banks in Indonesia using the systemic literature review (SLR) methodology following the PRISMA procedure. A comprehensive search of the Google Scholar Database was conducted using three key keywords: